Effects of Highly Absorbable Curcumin in Patients with Impaired Glucose Tolerance and Non-Insulin-Dependent Diabetes Mellitus. (23rd November 2019) - Funamoto, Masafumi; Shimizu, Kana; Sunagawa, Yoichi; Katanasaka, Yasufumi; Miyazaki, Yusuke; Kakeya, Hideaki; Yamakage, Hajime; Satoh-Asahara, Noriko; Wada, Hiromichi; Hasegawa, Koji; Morimoto, Tatsuya
Abstract : Oxidative stress is enhanced by various mechanisms. Serum oxidized low-density lipoprotein (LDL) is a useful prognostic marker in diabetic patients with coronary artery disease. To examine the effects of Theracurmin®, a highly absorbable curcumin preparation, on glucose tolerance, adipocytokines, and oxidized LDL, we conducted a double-blind placebo-controlled parallel group randomized trial in patients with impaired glucose tolerance or non-insulin-dependent diabetes mellitus. We randomly divided the patients with impaired glucose tolerance or non-insulin-dependent diabetes mellitus and stable individuals into the placebo group and the Theracurmin® (180 mg daily for 6 months) group. Of the 33 patients analyzed, 18 (14 males and 4 females) were administered placebo and 15 (9 males and 6 females) were administered Theracurmin®. The patient characteristics did not differ between the two groups. The primary endpoint, HbA1c, did not differ significantly between the two groups. However, the level of α 1-antitrypsin-low-density lipoprotein (AT-LDL), the oxidized LDL, significantly increased (p = 0.024 ) in the placebo group from the beginning of the trial up to 6 months, although there was no such change in the Theracurmin® group. The percentage change in BMI from the beginning of the trial up to 6 months tended to be higher in the Theracurmin® group than in the placebo group. Patients in the Theracurmin® group tended to have a larger percentage change in adiponectin and LDL-C than those in the placebo group. Patients in the Theracurmin® group showed a smaller percentage change in AT-LDL than those in the placebo group. This study suggests that the highly absorbable curcumin could potentially inhibit a rise in oxidized LDL in patients with impaired glucose tolerance or non-insulin-dependent diabetes mellitus. This trial is registered with UMIN000007361 .